PWE-229 Innovations in enterocutaneous fistula management: a systematic review. (22nd June 2015) - Dastur, JK; Nachiappan, S; Maeda, Y; Warusavitarne, J; Vaizey, C
Abstract : Introduction: Enterocutaneous fistulas are defined as abnormal communications between the gastrointestinal tract and the skin which may occur in various disease processes or iatrogenically. Patients who suffer with this condition manifest signs and symptoms of fluid and electrolyte imbalance, malnutrition and pain. Despite improvements in management and treatment modalities, mortality and morbidity rates remain high. This review aims to report on treatment innovations in this specialised field since 1980. Method: A systematic review of studies reporting on techniques and modalities in ECF treatment was undertaken. Studies reporting on treatment of ECFs in inflammatory bowel disease settings, and negative pressure wound management modalities were excluded in this review. Results: Thirty-six studies met the inclusion criteria. 32 were case series with small numbers, one was a case controlled study and three were systematic reviews/meta analysis. The newer modalities that have been described fell into the following categories: endoscopic (eight case series), surgical (six case series), percutaneous techniques (six case series and one case controlled study), other therapies (two case series) and pharmacological (10 case series and three systematic reviews/meta-analysis). Conclusion: These studies describe the newer modalities of ECF management. There is a paucity of randomised controlled trials due to the tenuous and protracted treatment requirements for this condition. The current standard of parenteral nutrition, control of sepsis, fluid and electrolyte homeostasis, wound care and a carefully timed definitive surgical procedure, form the core of its treatment. The described techniques generally attempt to reduce fistula output or mechanically occlude the fistulous tract. The newer modalities are not well-established and in most cases, act as adjuncts to the current standard therapies in ECF management. This review enables clinicians to objectively explore available therapies to treat this difficult condition and may allow for targeted approaches to be utilised in treating these patients. Disclosure of interest: None Declared.